2018
DOI: 10.11606/s1518-8787.2018052000103
|View full text |Cite
|
Sign up to set email alerts
|

Falls among older adults in the South of Brazil: prevalence and determinants

Abstract: OBJECTIVE Evaluate the prevalence and the factors associated with the occurrence of falls among older adults.METHODS A cross-sectional study with a representative sample of 1,451 elderly residents in the urban area of Pelotas, RS, in 2014. A descriptive analysis of the data was performed and the prevalence of falls in the last year was presented. The analysis of demographic, socioeconomic, behavioral and health factors associated with the outcome was performed using Poisson regression with adjustment for robus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
3
33

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(83 citation statements)
references
References 42 publications
(36 reference statements)
3
41
3
33
Order By: Relevance
“…Regarding the functionality evaluated by the Katz and Lawton and Brody Scales in this study, the independent elderly people to perform daily life activities had the lowest percentage of caregiver presence, while the most dependent had a higher percentage. It is known that the lower the functionality of the elderly, the greater the need for care, with multiple tasks, on a frequent basis, often requiring the total dedication of the caregiver (12) , especially if the older person present some type of dementia, as observed in this study.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Regarding the functionality evaluated by the Katz and Lawton and Brody Scales in this study, the independent elderly people to perform daily life activities had the lowest percentage of caregiver presence, while the most dependent had a higher percentage. It is known that the lower the functionality of the elderly, the greater the need for care, with multiple tasks, on a frequent basis, often requiring the total dedication of the caregiver (12) , especially if the older person present some type of dementia, as observed in this study.…”
Section: Discussionmentioning
confidence: 58%
“…The impairment of the functional capacity of individuals over 60 years old directly affects the quality of life, as well as simultaneously reaching the family, the community and the health system in which it is inserted. It is observed that the greater the difficulty in performing the basic activities of daily living, the more dependent this elderly is (12) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Em relação ao autorrelato de quedas, a maior frequência foi observada entre o grupo das idosas. O fato corrobora com a literatura especializada 33 . Por outro lado, observou-se também que 1/3 do grupo de mulheres adultas mostraram histórico de queda.…”
Section: Discussionunclassified
“…Considering that many elderly individuals live in non-adapted houses 4,5 , falls may occur, at least in part, due to extrinsic factors such as poor illumination, slippery floor, lack of stair handrail, uneven ground, obstacles inside the house, tall mattress or bed high off the ground, and loose carpets [6][7] . Nevertheless, the incidence of falls among the elderly is also associated with illnesses such as cerebrovascular accident, diabetes, heart disease, osteoporosis, depressive symptoms and arthritis 5,8 . Other causes include improper footwear, use of excessively long clothes, alcohol consumption, and use of medications [9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%